MATERNAL GUT MICROBIOME AND ITS IMPACT ON FETAL OUTCOMES: A FOCUS ON MATERNAL NUTRITION - Aulia, Bianda; Ermamilia, Aviria; Sundjaya, Tonny; Pratiwi, Dessy (Ridwan Institute, 2025)
Background: During pregnancy, maternal microbiota transfer and modifiable factors such as diet may contribute to fetal development. This review aims to clarify how maternal gut microbiota and diet interact to influence fetal nutrition and long-term health outcomes. Methods: A literature review was conducted on PubMed, Scopus, and Google Scholar. The search focused on studies investigating the links between maternal gut microbiota composition, dietary patterns, microbial metabolites, and fetal nutrition outcomes. Keywords included “pregnancy”, “gut microbiota”, “nutrition”, “maternal diet”, and “fetal growth”. Results: The maternal gut microbiota undergoes notable changes in late pregnancy, and its composition can be further influenced by external factors. Maternal diet and microbial transfer may impact fetal immune, metabolic, and neurodevelopment processes. Short-chain fatty acids and trimethylamine N-oxide are among key microbial metabolites implicated in fetal development. Although probiotic and prebiotic interventions during pregnancy show promise, current evidence remains limited and inconsistent across populations. Conclusion: Optimizing maternal gut microbiota through diet may support fetal nutrition and developmental outcomes. However, more longitudinal and ethnically diverse studies are needed.